Question
upstudy study bank question image url

Three consecutive terms of a geometric series are given in terms of a constant \( x \). \( U_{3}=(x+5), U_{4}=(4 x-1) \) and \( U_{5}=(2 x+3) \). Find the sum to infinity of the series. (Correct to four significant figures).

Ask by Vaughan Bond. in Ghana
Feb 15,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The sum to infinity of the series is 6.075.

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Beyond the Answer

To solve for the sum to infinity of the geometric series given the terms \( U_{3}=(x+5), U_{4}=(4x-1) \), and \( U_{5}=(2x+3) \), we first need to find the common ratio \( r \) of the series. The common ratio \( r \) can be found using the formula for consecutive terms in a geometric series, given by: \[ r = \frac{U_{n+1}}{U_n} \] Thus, we can set up the following equations from our terms: 1. From \( U_3 \) and \( U_4 \): \[ r = \frac{U_4}{U_3} = \frac{4x - 1}{x + 5} \] 2. From \( U_4 \) and \( U_5 \): \[ r = \frac{U_5}{U_4} = \frac{2x + 3}{4x - 1} \] Setting these two expressions for \( r \) equal gives us the equation: \[ \frac{4x - 1}{x + 5} = \frac{2x + 3}{4x - 1} \] Cross-multiplying yields: \[ (4x - 1)^2 = (2x + 3)(x + 5) \] Expanding both sides: \[ 16x^2 - 8x + 1 = 2x^2 + 10x + 3x + 15 = 2x^2 + 13x + 15 \] Bringing all terms to one side results in: \[ 16x^2 - 8x + 1 - 2x^2 - 13x - 15 = 0 \] \[ 14x^2 - 21x - 14 = 0 \] Dividing the entire equation by 7 simplifies it: \[ 2x^2 - 3x - 2 = 0 \] Now we can factor this quadratic: \[ (2x + 1)(x - 2) = 0 \] Thus, we have two possible solutions: \[ x = -\frac{1}{2} \quad \text{or} \quad x = 2 \] Next, we need to calculate \( U_3, U_4, U_5 \) to determine the value of the common ratio \( r \) for valid \( x \). 1. If \( x = 2 \): \[ U_3 = 2 + 5 = 7, \quad U_4 = 4(2) - 1 = 7, \quad U_5 = 2(2) + 3 = 7 \] The ratio is: \[ r = \frac{7}{7} = 1 \] The series would not converge, so we discard this solution. 2. If \( x = -\frac{1}{2} \): \[ U_3 = -\frac{1}{2} + 5 = \frac{9}{2}, \quad U_4 = 4(-\frac{1}{2}) - 1 = -3, \quad U_5 = 2(-\frac{1}{2}) + 3 = 2 \] The ratio becomes: \[ r = \frac{U_4}{U_3} = \frac{-3}{\frac{9}{2}} = -\frac{6}{9} = -\frac{2}{3} \] To find the sum to infinity of a geometric series, the formula is: \[ S_{\infty} = \frac{U_3}{1 - r} \] Where \( r \) must be less than 1 in absolute terms: \[ S_{\infty} = \frac{\frac{9}{2}}{1 - (-\frac{2}{3})} = \frac{\frac{9}{2}}{1 + \frac{2}{3}} = \frac{\frac{9}{2}}{\frac{5}{3}} = \frac{9}{2} \times \frac{3}{5} = \frac{27}{10} = 2.7 \] Final answer: \[ \boxed{2.700} \] (to four significant figures).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy